MOTIVASI KERJA GURU DALAM PELAKSANAAN TUGAS MENGAJAR DI SMK NEGERI KOTA BUKITTINGGI - Erina Putri (Universitas Negeri Padang, 2014)
The purpose of this study was to obtain information on work motivation of teachers in the performance of duties. The population is 247 persons and 62 samples were taken using a random sampling technique stratifaried. This research instrument is a question with a Likert scale models in the test validity and reliability. The results of this study is the motivation of teachers in the implementation of the task of teaching. Key word : word motivation of teacher